Triple –E Vessels: Tonnage Measurement and Suez Canal Dues Assessment - Elsayed Hussein Galall (Renewable Energy and Sustainable Development)
Container is growing faster than GDP, Shipping lines always attempt to augment efficiency by reducing cost and by attracting larger volumes of containers. As a result rising container freight rates the lines have been driven to increase economic of scale, by building mega ships and fewer mere efficient port calls. In 2011 Maersk line ordered up to 20 new “Triple- E “Class of container vessels delivers between 2013- 2015. These class of mega container vessels have its way through Suez Canal, other companies CMA, CGM also ordered this type of mega container vessels, in order to reach higher profits due to the achieved economics of scale It is believed that 20000 TEU could be the next target size. Present mega container fleet and any future feasible potential vessel capacity expansion more than 18000 TEU put Suez Canal route in strong competitive position. Meanwhile Panama Canal will not be able to handle vessels larger than 12600 TEU even after its expansion in 2015.